The Modified Kimura's Technique for the Treatment of Duodenal Atresia - Biagio Zuccarello; Antonella Spada; Antonio Centorrino; Nunzio Turiaco; Maria Rosaria Chirico; Saveria Parisi (Hindawi Limited, 2009)
Background/Purpose. Kimura's diamond-shaped-duodenoduodenostomy (DSD) is a known technique for the correction of congenital intrinsic duodenal obstruction. We present a modification of the technique and review the advantages of this new technique. Methods. From 1992 to 2006, 14 newborns were treated for duodenal atresia. We inverted the direction of the duodenal incisions: a longitudinal incision was made in the proximal duodenum while the distal was opened by transverse incision. Results. Our "inverted-diamond-shaped-duodenoduodenostomy" (i-DSD) allowed postoperative oral feeding to start on days 2 to 3, peripheral intravenous fluids discontinuity on days 3 to 8 (median values 3.6); time to achieve full oral feeds on days 8 to 12 (median values 9.4); the length of hospitalisation ranged from 10 and 14 days (median value 11.2). No complications related to the anastomosis, by Viz leakage, dehiscence, biliary stasis, or stenosis were observed. Conclusions. The i-DSD provides a safe procedure to protect the ampulla of Vater from injury and avoids any formation of a blind loop. The results show that patients who have i-DSD achieve full oral feeds in a very short time period and, consequently, the length of hospitalisation is also significantly reduced.